The effect of fatty acid’s dielectric constant in the generation of surface plasmons using numerical attenuated total reflection (ATR) (International Journal of Scientific Research and Management (IJSRM), 2023)
The surface plasmons were collective excitation of free charges which can be generated at the interface between metal and dielectrics. The active material was metal which provided free charges while dielectrics was passive material which maintained the electric fields at the interface. One of the most effective method to generate surface plasmons was attenuated total reflection (ATR). The basic concept of this method was total internal reflection. Hence, it required a high index prism, such as thallium halogenide. The ATR method can be done numerically by deriving ATR reflectivity. In the process of derivation, we should consider the reflectivity at the all involved interfaces. Then, the ATR reflectivity can be obtained by scanning frequency at the certain interval near the surface plasmon frequency. In this report, we study the surface plasmon which was generated at the interface between gold and fatty acid. We analysed the effect of fatty acid’s dielectric constant to the ATR spectroscopy. We found that the decrease of the fatty acid’s permittivity increase the surface plasmon resonance (SPR frequency and decrease the reflectivity at this resonance frequency.